2012
DOI: 10.1080/10291954.2012.11435164
|View full text |Cite
|
Sign up to set email alerts
|

The corporate use of derivatives: a survey of South Africa’s large listed non-financial firms

Abstract: This paper presents the results of a comparative questionnaire survey of derivative use by South African companies. The objective was to determine the extent of derivative use and to examine how and why companies use derivatives. Derivative use by South African companies compares favourably to the level of derivative use in developed countries. The risk most often hedged is currency exposure followed by interest rate risk. Commodity producers tend to hedge commodity price risk. Companies mainly use forwards to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…This difference in derivative use is placed in stark contrast in Figure 2. This study found further that the percentage of companies using derivatives for South Africa is significantly lower than that recorded by Correia et al (2012) and Modack, et al (2012) which reported derivative use at a rate of 90% and 93% respectively. This difference in derivative use is mostly explained by the fact that the sample of companies used in the Correia et al (2012) and Modack, et al (2012) surveys were made up of the 100 largest JSE listed companies, whereas this study analysed derivative use by all listed companies in South Africa and therefore includes many smaller companies.…”
Section: Derivative Usagesupporting
confidence: 63%
See 4 more Smart Citations
“…This difference in derivative use is placed in stark contrast in Figure 2. This study found further that the percentage of companies using derivatives for South Africa is significantly lower than that recorded by Correia et al (2012) and Modack, et al (2012) which reported derivative use at a rate of 90% and 93% respectively. This difference in derivative use is mostly explained by the fact that the sample of companies used in the Correia et al (2012) and Modack, et al (2012) surveys were made up of the 100 largest JSE listed companies, whereas this study analysed derivative use by all listed companies in South Africa and therefore includes many smaller companies.…”
Section: Derivative Usagesupporting
confidence: 63%
“…Whilst Sprcic 2007 Bodnar et al ( and 2003 and Correia et al (2012) found OTC Forwards to be the most preferred instrument for the management of foreign exchange exposure, Alkeback and Hagelin (1999) found that firms in Sweden use a wider range of instruments to manage currency exposure and companies use OTC Forwards, Exchange-traded Forwards, Swaps and Futures. The most preferred instruments to manage currency risks in Malaysia is cited as OTC Forwards (Ameer et al 2011) and this is due to the greater flexibility of Forward foreign-exchange contracts (which are available from licensed local banks) over other standardized foreign-exchange Options and Futures contracts.…”
Section: Figure 1 Types Of Risk Exposures Hedged By Companiesmentioning
confidence: 99%
See 3 more Smart Citations